Graft copolymerization of 4-vinylpyridine on to chitosan - I. By ceric ion initiation - Caner, H; Hasipoglu, H; Yilmaz, O; Yilmaz, E (Pergamon-Elsevier Science Ltd, 1998)
The grafting of poly(4-vinylpyridine) (P4VP) on to chitosan by eerie ion initiation was studied under homogeneous conditions in 1% acetic acid solution. The products were characterized by infrared (IR) spectrometry and differential scanning calorimetry (DSC). The effects of monomer concentration and temperature on per cent grafting were studied. Per cent grafting was observed to increase with the amount of monomer, showing a tendency to level off at a 4VP concentration of 0.53 mol/l. Per cent grafting increased with temperature up to 70 degrees C and then decreased to 80 degrees C. Solubility tests carried out on grafted chitosan samples revealed that the samples swelled in 1:1 and 1:2 acetic acid:ethanol solvent mixtures. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: Chitin